Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Pada Hotel Ollino Garden Malang) - Saputra, Erick Sebastian; Pinando, Sugeng (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aim to determine the effect of variable dimensions of service quality on customer satisfaction Ollino Garden Hotel Malang simultaneously and partially as well as to prove whether physical evidence is a dominant variable affecting customer satisfaction. To determine how much influence the dependent variable (the variable dimensions of service quality) of the independent variable (customer satisfaction) used multiple linear regression analysis. From the results of multiple regression analysis it is known that other variables not participate researched a great influence on customer satisfaction Ollino Garden Hotel Malang. This suggests that the quality of service provided Ollino Garden Hotel Malang has not been able to contribute well in the form of customer satisfaction. Besides the physical evidence variable not be an dominant variable in the form of customer satisfaction Ollino Garden Hotel Malang but guarantee a variable that has variables that can form the dominant influence customer satisfaction. Keywords: Influence, Service Quality, Customer Satisfaction